Monitoring Antarctic krill (Euphausia superba) distribution in the Southern Ocean: environmental DNA (eDNA) adds to the toolbox - Leonie Suter; Leonie Suter; Alicia Burns; Alicia Burns; Alicia Burns; Sophie Bestley; Sophie Bestley; Jez Bird; Madeleine J. Brasier; Madeleine J. Brasier; Martin Cox; Martin Cox; et al. (Frontiers in Marine Science)
Antarctic krill (Euphausia superba Dana) is a key species of the Southern Ocean ecosystem, immensely abundant and targeted by the krill fishery. For their sustainable management, krill distribution and biomass estimates are required, typically achieved through acoustic-trawl surveys. We explore how krill environmental DNA (eDNA) can contribute to our understanding or Antarctic krill habitat and distribution. We collected eDNA samples by filtering five liters of seawater per sample in the East Antarctic Southern Ocean from the surface (5 m depth) and seafloor (381–4422 m depth, total n = 110). We used quantitative PCR to measure Antarctic krill eDNA abundance and age, and eDNA metabarcoding to detect any krill species. This eDNA data was compared to acoustic, visual and trawl detections of Antarctic krill. Antarctic krill eDNA was common in surface samples and largely overlapped with visual and trawl detections. Highest eDNA concentrations were detected above krill swarms, with concentrations declining with increasing distance from swarms. Near recent eDNA sampling locations, krill swarms were more likely acoustically detected than near old eDNA sampling locations. Antarctic krill detections were less common in seafloor locations, and detections were concentrated in the continental slope area to the south of the survey area, both for visual detections and for recent eDNA detections. Both methods detected Antarctic krill at great depths (recent eDNA: 4300 m; visual: 3080 m). In both eDNA and trawl data, Antarctic krill was the dominant krill species, followed by Thysanoessa macrura G.O. Sars, which was particularly abundant in larval stages throughout the survey area, including at Antarctic krill swarm locations. We recommend the inclusion of eDNA data for Antarctic krill distribution estimates and understanding of habitat use, particularly in difficult-to-access areas, such as under ice or benthic habitats.